Asymmetric battery having semi-solid cathode and high energy density anode

Semi-solid positive electrodes with simplified manufacturing processes address the limitations of conventional batteries by increasing active material loading and reducing inert components, resulting in high energy density batteries.

JP2024173934AInactive Publication Date: 2024-12-1324M TECHNOLOGIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024143414
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2013-03-15
Filing Date
2024-08-23
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional battery manufacturing methods result in low energy density due to limited electrode thickness, high inert component fraction, and complex, costly processes, limiting the utilization of high-capacity anode materials.

Method used

Development of semi-solid positive electrodes thicker than negative electrodes, with a simplified manufacturing process, allowing higher active material loading densities and reduced inert component contribution, paired with high-capacity anodes such as silicon or tin.

Benefits of technology

Achieves volumetric energy densities greater than 600 Wh/L by optimizing the ratio of active to inactive materials, reducing manufacturing costs, and enhancing overall battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024173934000001_ABST
    Figure 2024173934000001_ABST
Patent Text Reader

Abstract

To provide devices, systems, and methods of producing high energy density batteries having a semi-solid cathode that is thicker than the anode.SOLUTION: An electrochemical cell can include a positive electrode current collector, a negative electrode current collector, and an ion-permeable membrane disposed between the positive electrode current collector and the negative electrode current collector. The ion-permeable membrane is spaced a first distance from the positive electrode current collector and at least partially defines a positive electroactive zone. The ion-permeable membrane is spaced a second distance from the negative electrode current collector and at least partially defines a negative electroactive zone. The second distance is less than the first distance. A semi-solid cathode that includes a suspension of an active material and a conductive material in a nonaqueous liquid electrolyte is disposed in the positive electroactive zone, and an anode is disposed in the negative electroactive zone.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to and the benefit of U.S. Provisional Application No. 61 / 787,372, filed March 15, 2013, entitled "Asymmetric Battery Having a Semi-solid Cathode and High Energy Density Anode," the entire disclosure of which is incorporated herein by reference.

[0002]

[0002] The embodiments described herein relate generally to asymmetric batteries having a high energy density anode, and more particularly to apparatus, systems, and methods for producing high energy density batteries having a semi-solid cathode that is thicker than the anode. [Background technology]

[0003]

[0003] Batteries are typically constructed with solid electrodes, separators, electrolytes, and auxiliary components such as packaging, thermal management, cell balancing, compaction of current carriers into terminals and / or other such components. Such conventional battery manufacturing methods generally involve complex and expensive manufacturing steps, such as casting of electrodes, and are only suitable for electrodes of limited thickness, such as typically less than 100 μm. Such known methods for producing electrodes of limited thickness result in batteries with low capacity, low energy density, and a high ratio of inactive components to active materials. In other words, the non-energy storage elements of the completed device, i.e., the separator and current collector, comprise a relatively high fixed volume or mass fraction of the device, thereby reducing the overall energy density of the device. Summary of the Invention [Problem to be solved by the invention]

[0004]

[0004] Therefore, simplification and reduction in manufacturing costs, reduction in inactive components in the electrodes and finished battery, and increase in energy density and overall performance are perennial goals in the development of energy storage systems. [Means for solving the problem]

[0005]

[0005] The embodiments described herein generally relate to devices, systems, and methods for producing high energy density batteries having a semi-solid positive electrode that is thicker than a negative electrode. In some embodiments, an electrochemical cell can include a positive electrode current collector, a negative electrode current collector, and an ion-permeable membrane disposed between the positive electrode current collector and the negative electrode current collector. The ion-permeable membrane is spaced a first distance from the positive electrode current collector and at least partially defines a positive electroactive zone. The ion-permeable membrane is spaced a second distance from the negative electrode current collector and at least partially defines a negative electroactive zone. The second distance is less than the first distance. A semi-solid positive electrode including a suspension of an active material and a conductive material in a non-aqueous liquid electrolyte is disposed in the positive electroactive zone, and a negative electrode is disposed in the negative electroactive zone. [Brief description of the drawings]

[0006] [Figure 1] 1 is a schematic diagram of an electrochemical cell according to one embodiment. [Diagram 2]

[0007] FIG. 1 is a schematic diagram of a symmetric electrochemical cell according to one embodiment. [Diagram 3]

[0008] FIG. 1 is a schematic diagram of an asymmetric electrochemical cell according to one embodiment. [Figure 4]

[0009] FIG. 1 is a schematic diagram of an asymmetric electrochemical cell according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007]

[0010] The embodiments described herein generally relate to devices, systems, and methods for producing high energy density batteries having a semi-solid positive electrode that is thicker than a negative electrode. In some embodiments, an electrochemical cell can include a positive electrode current collector, a negative electrode current collector, and an ion-permeable membrane disposed between the positive electrode current collector and the negative electrode current collector. The ion-permeable membrane is spaced a first distance from the positive electrode current collector and at least partially defines a positive electroactive zone. The ion-permeable membrane is spaced a second distance from the negative electrode current collector and at least partially defines a negative electroactive zone. The second distance is less than the first distance. A semi-solid positive electrode comprising a suspension of active and conductive materials in a non-aqueous liquid electrolyte is disposed within the positive electroactive zone, and a negative electrode is disposed within the negative electroactive zone.

[0008]

[0011] Batteries for consumer electronics have been gradually increasing in energy density with the advancement of lithium-ion battery technology. The stored energy or charge capacity of a manufactured battery is determined by (1) the specific charge capacity of the active material (mAh / g), (2) the volume of the electrodes (cm 3 ) (i.e., the product of the electrode thickness, the electrode area, and the number of layers (stacks)); and (3) the loading of active material in the electrode media (e.g., 1 cm 3 The capacity of a battery is a function of the area charge capacity (grams of active material per unit of electrode medium). Therefore, to increase commercial attractiveness (e.g., increased energy density and decreased cost), batteries are generally designed to have higher areal charge capacity (mAh / cm 2) is desirable. The areal charge capacity can be increased, for example, by using active materials with greater specific charge capacity, by increasing the relative percentage (i.e., "loading") of active charge storage material in the overall electrode formulation, and / or by increasing the relative percentage of electrode material used in any given battery form factor. Stated differently, increasing the ratio of active charge storage components (e.g., electrodes) to inactive components (e.g., separator and current collector) increases the overall energy density of the battery by removing or reducing components that do not contribute to the battery's overall performance. One way to achieve increased areal charge capacity, and thus reduced relative percentage of inactive components, is to increase the thickness of the electrodes.

[0009]

[0012] In some embodiments, higher energy density and capacity can be achieved, for example, by improving the materials used in the anode and / or cathode and / or by increasing the thickness of the anode / cathode (i.e., increasing the ratio of active material to inactive material). One of the latest materials used in anodes for electronics applications is silicon (Si), tin (Sn), silicon alloys, or tin alloys, for example, due to their high capacity and low voltage. Typically, this high capacity active material is mixed with graphite due to its high first charge capacity and associated first charge irreversible capacity. Silicon has a first charge theoretical capacity of 4200 mAh / g and an irreversible capacity of more than 300 mAh / g. Thus, a typical anode using Si contains a mixture of silicon and graphite to reduce the irreversible capacity. In addition, silicon experiences a very large volume change during lithium insertion that causes the volume of the material to grow by more than 300%. To limit this large volume expansion, current high capacity anodes use 10-20% silicon in the anode mix, resulting in an anode with an overall capacity of about 700 to about 4200 mAh / g.

[0010]

[0013] Conventional positive electrode compositions have capacities of approximately 150-200 mAh / g and cannot be thicker than 200 μm because conventional electrodes fabricated using a high-speed roll-to-roll calendaring process tend to delaminate from the flat current collector when thicker than about 200 μm. Furthermore, thicker electrodes result in higher cell impedance, which reduces energy efficiency (see, for example, Yu et al., "Effect of electrode parameters on LiFePO 4 As described in "High-capacity anodes" (J. Electrochem. Soc., Vol. 153, A835-A839, 2006), in order to match high-capacity anodes with conventional positive electrodes, current state-of-the-art batteries have focused on reducing the thickness of the anode. For example, anodes having thicknesses of about 40-50 μm and even less have been developed. Such thin coatings of these anode materials are beginning to approach the thickness level of a single graphite particle. The thickness and associated loading density limitations of conventional coating processes have hindered the development of batteries that fully utilize the large capacity available in high-energy anodes.

[0011]

[0014] The semi-solid positive electrodes described herein (i) can be made thicker (e.g., greater than 200 μm, up to 2000 μm or more) due to reduced bending and higher electronic conductivity of the semi-solid electrode, (ii) can have a higher active material loading, and (iii) can be made with a simplified manufacturing process using less equipment, thereby reducing the volume, mass, and cost contribution of inactive components to active components. Examples of semi-solid positive electrodes having thicknesses greater than 200 μm without adversely affecting impedance, energy efficiency, energy density, or capacity are described in U.S. patent application entitled "Semi-Solid Electrodes Having High Rate Capability," filed on the same date herewith, and having attorney docket number 24MT-008 / 01US, the disclosure of which is incorporated herein by reference and attached hereto as Appendix A. Examples of systems and methods that can be used to prepare the semi-solid compositions and / or electrodes are described in U.S. patent application Ser. No. 24MT-003 / 04US, filed on the same day as this application, entitled "Electrochemical Slurry Compositions and Methods for Preparing the Same," the entire disclosure of which is incorporated herein by reference and attached hereto as Appendix B.

[0012]

[0015] Semi-solid positive electrodes can be made much thicker (e.g., greater than 200 μm) than conventional electrodes, allowing for higher loading densities, so that the semi-solid positive electrodes can be more effectively paired with high-energy negative electrodes. In other words, thicker semi-solid positive electrodes allow for 3, 4, 5, or more times higher active material loading densities than conventional coated electrodes. Thicker semi-solid positive electrodes with higher loading densities can be paired with negative electrodes using silicon, tin, or other high-energy negative electrode materials without the need to maintain thin negative electrodes and / or loading densities. High-capacity negative electrodes can be made by conventional coating methods and can have high loading densities approaching the maximum active material loading densities of conventional electrodes using binders, and as a result can still be matched / balanced with the positive electrode. Pairing a semi-solid positive electrode with a high-capacity negative electrode can result in a cell with a volumetric energy density of greater than 600 Wh / L or more. In some embodiments, the negative electrode can be a semi-solid negative electrode made with a high-energy negative electrode material, similarly as described for the semi-solid positive electrode.

[0013]

[0016] In some embodiments, the electrode materials described herein can be flowable semi-solid compositions or condensed liquid compositions. A flowable semi-solid electrode can include a suspension of electrochemically active material (anode particles or particulates) and optionally an electronically conductive material (e.g., carbon) in a non-aqueous liquid electrolyte. Stated another way, the active electrode particles and the conductive particles are co-suspended in the electrolyte to produce a semi-solid electrode. The negative electrode includes a high energy negative electrode material, such as silicon, tin, aluminum, titanium oxide, or any other high capacity material, alloys or combinations thereof. In some embodiments, the negative electrode can be formed using a conventional coating / calendering process. In some embodiments, the negative electrode can be a semi-solid negative electrode including high energy negative electrode particles and carbon (e.g., graphite) particles co-suspended in the electrolyte to produce a semi-solid negative electrode. Examples of battery architectures using semi-solid suspensions are described in International Patent Publication No. 2012 / 024499, entitled "Stationary, Fluid Redox Electrode," and International Patent Publication No. 2012 / 088442, entitled "Semi-Solid Filled Battery and Method of Manufacture," the entire disclosures of which are incorporated herein by reference.

[0014]

[0017] As used herein, the terms "about" and "approximately" generally mean + / - 10% of the specified value, for example, about 250 μm would include 225 μm to 275 μm, and about 1000 μm would include 900 μm to 1100 μm.

[0015]

[0018] As used herein, the term "semi-solid" refers to a material that is a mixture of liquid and solid phases, such as, for example, a particulate suspension, a colloidal suspension, an emulsion, a gel, or a micelle.

[0016]

[0019] The term "condensed ion-storing liquid" or "condensed liquid" as used herein refers to a liquid that is itself redox active, rather than simply a solvent as in the case of an aqueous flow cell semi-solid positive or negative electrode. Of course, such liquid formats include mixing with such diluents to form low melting liquid phases, emulsions, or micelles that contain the ion-storing liquid, and may also be diluted by or mixed with other non-redox active liquids that are diluents or solvents.

[0017]

[0020] As used herein, the terms "activated carbon network" and "networked carbon" refer to the general qualitative state of an electrode. For example, an electrode having an activated carbon network (or networked carbon) is one in which the carbon particles within the electrode exhibit individual particle morphologies and arrangements relative to one another that promote electrical contact and electrical conductivity between the particles. Conversely, the terms "unactivated carbon network" and "unnetworked carbon" refer to electrodes in which the carbon particles exist as individual particle islands or as multi-particle agglomerated islands that are not sufficiently connected to provide sufficient electrical conduction through the electrode.

[0018]

[0021] As used herein, the term "volumetric energy density" refers to the amount of energy (e.g., Wh) stored in an electrochemical cell per unit volume (e.g., L) of materials necessary for the electrochemical cell to operate, such as electrodes, separators, electrolytes, and current collectors. Specifically, materials used to package the electrochemical cell are excluded from the volumetric energy density calculation.

[0019]

[0022] In some embodiments, an electrochemical cell for storing energy includes a positive electrode current collector, a negative electrode current collector, and an ion-permeable membrane disposed between the positive electrode current collector and the negative electrode current collector. The ion-permeable membrane is spaced a first distance from the positive electrode current collector and at least partially defines a positive electroactive zone. The ion-permeable membrane is spaced a second distance from the negative electrode current collector and at least partially defines a negative electroactive zone. The second distance is less than the first distance. A semi-solid positive electrode including a suspension of an active material and a conductive material in a non-aqueous liquid electrolyte is disposed in the positive electroactive zone, and a negative electrode is disposed in the negative electroactive zone. In some embodiments, the negative electrode can be a semi-solid negative electrode including a suspension of a high-capacity active material and a carbon material in a non-aqueous liquid electrolyte.

[0020]

[0023] In some embodiments, the negative electrode comprises at least one high capacity negative electrode material selected from silicon, bismuth, boron, gallium, indium, zinc, tin, antimony, aluminum, titanium oxide, molybdenum, germanium, manganese, niobium, vanadium, tantalum, iron, copper, gold, platinum, chromium, nickel, cobalt, zirconium, yttrium, molybdenum oxide, germanium oxide, silicon oxide, silicon carbide, any other high capacity material, or alloys thereof, and any combination thereof.

[0021]

[0024] In some embodiments, the first distance is at least about 250 μm, hi some embodiments, the first distance is about 300 μm, about 350 μm, about 400 μm, about 450 μm, about 500 μm, about 600 μm, about 700 μm, about 800 μm, about 900 μm, about 1000 μm, about 1500 μm, and up to about 2000 μm, including all thicknesses therebetween.

[0022]

[0025] In some embodiments, the first distance is about 250 μm to about 2000 μm, about 300 μm to about 2000 μm, about 350 μm to about 2000 μm, 400 μm to about 2000 μm, about 450 μm to about 2000 μm, about 500 to about 2000 μm, about 250 μm to about 1500 μm, about 300 μm to about 1500 μm, about 350 μm to about 1500 μm, about 400 μm, inclusive of all ranges or any other distances therebetween. ~1500μm, 450μm~1500μm, 500~1500μm, 250μm~1000μm, 300μm~1000μm, 350μm~1000μm, 400μm~10 00μm, about 450μm to about 1000μm, about 500μm to about 1000μm, about 250μm to about 750μm, about 300μm to about 750μm, about 350μm to about 750μm, about 400μm to about 750μm, about 4 50μm to about 750μm, about 500μm to about 750μm, about 250μm to about 700μm, about 300μm to about 700μm, about 350μm to about 700μm, about 400μm to about 700μm, about 450μm to about 70 0μm, about 500μm to about 700μm, about 250μm to about 650μm, about 300μm to about 650μm, about 350μm to about 650μm, about 400μm to about 650μm, about 450μm to about 650μm, about 500μm The thickness of the slit is within the range of about 250 μm to about 600 μm, about 300 μm to about 600 μm, about 350 μm to about 600 μm, about 400 μm to about 600 μm, about 450 μm to about 600 μm, about 500 μm to about 600 μm, about 250 μm to about 550 μm, about 300 μm to about 550 μm, about 350 μm to about 550 μm, about 400 μm to about 550 μm, about 450 μm to about 550 μm, or about 500 μm to about 550 μm.

[0023]

[0026] In some embodiments, the second distance is within the range of about 30 μm to about 200 μm, about 40 μm to about 200 μm, about 50 μm to about 200 μm, about 60 μm to about 200 μm, about 70 μm to about 200 μm, about 100 μm to about 200 μm, about 150 μm to about 200 μm, about 200 μm to about 300 μm, about 200 μm to about 400 μm, or about 200 μm to about 500 μm, including all ranges or any other distances therebetween.

[0024]

[0027] In some embodiments, the negative electrode can include about 66 wt%-70 wt% Si, about 15 wt%-22 wt% Co, and about 4 wt%-12 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 15 wt%-20 wt% Ni, and about 10 wt%-15 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 15 wt% Fe, and about 15 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 20 wt% Ti, and about 10 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 15 wt% Mo, and about 15 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, 15 wt% Co, 5 wt% Ni, and about 10 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 10 wt% Co, about 10 wt% Ni, and about 10 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 5 wt% C, about 15 wt% Ni, and about 10 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 5 wt% Fe, about 10 wt% Ni, and about 15 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 5 wt% Fe, about 10 wt% Ni, and about 15 wt% C. In some embodiments, the negative electrode can include about 70 wt% Si, about 10 wt% Co, and about 5 wt% Ni. In some embodiments, the negative electrode can include about 74 wt% Si, 2 wt% Sn, and about 24 wt% Co. In some embodiments, the negative electrode can include about 73 wt% Si, about 2 wt% Sn, and about 25 wt% Ni. In some embodiments, the negative electrode can include about 70 wt% Si, 10 wt% Fe, about 10 wt% Ti, and about 10 wt% Co. In some embodiments, the negative electrode can include about 70 wt% Si, about 15 wt% Fe, about 5 wt% Ti, and about 10 wt% C. In some embodiments, the negative electrode can include about 74.67 wt% Si, 16 wt% Fe, 5.33 wt% Ti, and 4 wt% C. In some embodiments, the negative electrode can include about 55 wt% Si, 29.3 wt% Al, and about 15.7 wt% Fe.In some embodiments, the negative electrode can include, by weight, about 70 wt% Si, about 20 wt% C from precursors, and about 10 wt% graphite. In some embodiments, the negative electrode can include about 55 wt% Si, about 29.3 wt% Al, and about 15.7 wt% Fe. In some embodiments, the negative electrode can include about 60-62 wt% Si, about 16-20 wt% Al, about 12-14 wt% Fe, and about 8% Ti. In some embodiments, the negative electrode can include about 50 wt% Sn, about 27.3 wt%-35.1 wt% Co, about 5 wt%-15 wt% Ti, and about 7.7 wt%-9.9 wt% C. In some embodiments, the negative electrode can include about 50 wt% Sn, about 39-42.3 wt% Co, and about 7.7-11 wt% C. In some embodiments, the negative electrode can include about 35-70 mol% Si, about 1-45 mol% Al, about 5-25 mol% transition metal, about 1-15 mol% Sn, and about 2-15 mol% yttrium, a lanthanide element, an actinide element, or a combination thereof.

[0025]

[0028] In some embodiments, the negative electrode can include a tin metal alloy, such as, for example, Sn-Co-C, Sn-Fe-C, Sn-Mg-C, or La-Ni-Sn alloys. In some embodiments, the negative electrode can include an amorphous oxide, such as, for example, SnO or SiO amorphous oxide. In some embodiments, the negative electrode can include, for example, Sn-Si-Al-BO, Sn-Sb-SO, SnO 2 -P 2 O 5 , or SnO-B 2 O 3 -P 2 O 5 -Al 2 O 3 In some embodiments, the negative electrode can include a glassy negative electrode, such as, for example, CoO, SnO 2 , or V 2 O 5 In some embodiments, the negative electrode can include a metal oxide such as, for example, Li 3 N or Li2 It may include metal nitrides such as .6CoO.4N.

[0026]

[0029] In some embodiments, the negative electrode can be a single layer negative electrode that includes all the components of the negative electrode (e.g., active material, conductive material, electrolyte, and bulk layer) mixed together in that layer. In some embodiments, the negative electrode can include a multi-layer structure, e.g., multiple layers of bulk negative electrode material combined with a carbon material.

[0027]

[0030] In some embodiments, the electrochemical cell includes a semi-solid positive electrode comprising a suspension of active material and conductive material in a non-aqueous liquid electrolyte, the semi-solid positive electrode having a capacity of about 150-200 mAh / g and a thickness in the range of about 250 μm to about 2000 μm, and a negative electrode having a capacity in the range of about 700-1200 mAh / g and a thickness in the range of about 30 μm to about 600 μm. The negative electrode and the semi-solid positive electrode are separated by a separator disposed therebetween.

[0028]

[0031] In some embodiments, the negative electrode comprises an active negative electrode material selected from lithium metal, carbon, lithium-intercalated carbon, lithium nitride, lithium alloys, and lithium alloy forming compounds of silicon, bismuth, boron, gallium, indium, zinc, tin, antimony, aluminum, titanium oxide, molybdenum, germanium, manganese, niobium, vanadium, tantalum, gold, platinum, iron, copper, chromium, nickel, cobalt, zirconium, yttrium, molybdenum oxide, germanium oxide, silicon oxide, silicon carbide, any other high capacity material or alloys thereof, and any other combinations thereof.

[0029]

[0032] In some embodiments, the thickness of the positive electrode can be in the range of about 2 to about 6 times the thickness of the negative electrode. In some embodiments, the thickness of the positive electrode can be in the range of about 2 to about 5 times, about 2 to about 4 times, about 2 to about 3 times, about 3 to about 6 times, about 4 to about 6 times, or about 5 to about 6 times the thickness of the negative electrode.

[0030]

[0033] In some embodiments, the semi-solid positive electrode can include about 20% to about 75% by volume of active material. In some embodiments, the semi-solid positive electrode can include about 40% to about 75% by volume or about 60% to about 75% by volume of active material.

[0031]

[0034] In some embodiments, the semi-solid positive electrode can include about 0.5% to about 25% conductive material by volume. In some embodiments, the semi-solid positive electrode can include about 1.0% to about 6% conductive material by volume.

[0032]

[0035] In some embodiments, the semi-solid positive electrode can include about 25% to about 70% electrolyte by volume, hi some embodiments, the semi-solid positive electrode can include about 30% to about 50% or about 20% to about 40% electrolyte by volume.

[0033]

[0036] In some embodiments, the negative electrode is a solid negative electrode formed on a negative electrode current collector. In some embodiments, the negative electrode is a semi-solid negative electrode comprising about 50% to about 75% by volume of a carbonaceous active material, about 1% to about 10% by volume of a high energy capacity negative electrode material, about 0.5% to about 2% by volume of a conductive material, and about 20% to about 40% by volume of a non-aqueous liquid electrolyte. In some embodiments, the high capacity negative electrode material comprises at least one high capacity negative electrode material selected from silicon, silicon alloys, tin, tin alloys, aluminum, and titanium oxide.

[0034]

[0037] In some embodiments, the semi-solid negative electrode can include about 0% to about 75% active material by volume. In some embodiments, the semi-solid negative electrode can include about 40% to about 75% active material by volume, or about 50% to about 75% active material by volume.

[0035]

[0038] In some embodiments, the semi-solid negative electrode can include from about 0% to about 75% by volume of the high energy capacity material. In some embodiments, the semi-solid negative electrode can include from about 1% to about 30% by volume, from about 1% to about 20% by volume, from about 1% to about 10% by volume, or from about 1% to about 5% by volume of the high energy capacity material.

[0036]

[0039] In some embodiments, the semi-solid negative electrode can include about 0% to about 10% by volume of conductive material. In some embodiments, the semi-solid negative electrode can include about 1% to about 6% by volume or about 0.5% to about 2% by volume of conductive material.

[0037]

[0040] In some embodiments, the semi-solid negative electrode can include about 10% to about 70% electrolyte by volume. In some embodiments, the semi-solid negative electrode can include about 30% to about 50% electrolyte by volume, or about 20% to about 40% electrolyte by volume.

[0038]

[0041] In some embodiments, an electrochemical cell including a semi-solid positive electrode and a high-energy negative electrode can have a volumetric energy density of greater than about 600 Wh / L, greater than about 700 Wh / L, greater than about 800 Wh / L, greater than about 900 Wh / L, greater than about 1000 Wh / L, greater than about 1100 Wh / L, and up to about 1200 Wh / L.

[0039]

[0042] In some embodiments, the electrochemical cell can include a negative electrode and a semi-solid positive electrode material including about 60% to about 80% by weight of an active material, about 1% to about 6% by weight of a conductive material, and about 20% to about 40% by weight of a non-aqueous liquid electrolyte. A separator is disposed between the negative electrode and the semi-solid positive electrode such that the thickness of the positive electrode is at least about twice the thickness of the negative electrode. In some embodiments, the thickness of the positive electrode is at least about three times the thickness of the negative electrode. In some embodiments, the thickness of the positive electrode is at least about four times the thickness of the negative electrode. In some embodiments, the thickness of the positive electrode is at least about five times the thickness of the negative electrode.

[0040]

[0043] In some embodiments, the electrochemical cell includes a semi-solid positive electrode that can include about 60% to about 80% by weight of an active material, about 1% to about 6% by weight of a conductive material, and about 20% to about 40% by weight of a non-aqueous liquid electrolyte. The semi-solid positive electrode can have a thickness in the range of about 250 μm to about 2000 μm. The electrochemical cell also includes a negative electrode that can include a high charge capacity material and can have an overall capacity in the range of about 700 mAh / g to about 1200 mAh / g. The negative electrode can have a thickness in the range of about 20% to about 25% of the thickness of the positive electrode. The negative electrode and the semi-solid positive electrode are separated by a separator disposed therebetween.

[0041]

[0044] In some embodiments, a method of manufacturing an electrochemical cell includes transferring the anode semi-solid suspension to a negative electroactive zone defined at least in part by the anode current collector and an ion-permeable membrane spaced apart from the anode current collector. The method also includes transferring the cathode semi-solid suspension to a positive electroactive zone defined at least in part by the cathode current collector and an ion-permeable membrane spaced apart from the cathode current collector. The transfer of the anode semi-solid suspension to the anode compartment and the cathode semi-solid suspension to the cathode compartment can be performed such that the difference between the minimum and maximum distances between the anode current collector and the ion-permeable membrane is maintained within a predetermined tolerance. Additionally, the thickness of the positive electroactive zone is substantially greater than the thickness of the negative electroactive zone. In some embodiments, the positive electroactive zone can be about 2, 3, 4, or 5 times thicker than the negative electroactive zone. The method further includes sealing the negative and positive electroactive zones.

[0042]

[0045] In some embodiments, a method of manufacturing an electrochemical cell includes positioning an injection nozzle within an electrode defined at least in part by a current collector and an ion-permeable membrane. A semi-solid positive electrode material is transferred to an electroactive zone by the injection nozzle. The injection nozzle is then withdrawn from the electrode chamber for at least a portion of the transfer, and the electrode chamber is then sealed.

[0043]

[0046] 1 shows a schematic diagram of an electrochemical cell 100 for storing large amounts of energy. The electrochemical cell 100 includes a positive current collector 110, a negative current collector 120, and a separator 130 disposed between the positive current collector 110 and the negative current collector 120. The positive current collector 110 is spaced a first distance t from the separator 130. 1 The negative current collector 120 is spaced a second distance t from the separator 130 to at least partially define a positive electroactive zone. 2 The first distance t 1 is effectively t 2 The semi-solid positive electrode 140 is disposed within the positive electroactive zone, the negative electrode 150 is disposed within the negative electroactive zone, and the first distance t 1 defines the thickness of the positive electrode 140, and the second distance t 2 defines the thickness of the negative electrode 150 .

[0044]

[0047] The positive current collector 110 and the negative current collector 120 can be any current collector that is electronically conductive and electrochemically inert under the operating conditions of the cell. Typical current collectors for lithium batteries include copper, aluminum, or titanium for the negative current collector and aluminum for the positive current collector in the form of sheet or mesh or any combination thereof.

[0045]

[0048] The current collector material can be selected to be stable at the operating potentials of the positive and negative electrodes of the electrochemical cell 100. For example, in a non-aqueous lithium system, the positive current collector can be aluminum or Li / Li +The negative current collector may comprise aluminum coated with a conductive material that is not electrochemically dissolved at an operating potential of 2.5 to 5.0 V with respect to the negative current collector. Such materials include platinum, gold, nickel, conductive metal oxides such as vanadium oxide, and carbon. The negative current collector may comprise copper or other metals that do not form alloys or intermetallic compounds with lithium, carbon, and / or coatings including such materials disposed on other conductors.

[0046]

[0049] The separator 130 can be any suitable separator that acts as an ion-permeable membrane, i.e., allows for the exchange of ions while maintaining physical separation of the positive electrode 140 and negative electrode 150 compositions. For example, the separator 130 can be any conventional membrane capable of ion transport. In some embodiments, the separator 130 is a liquid-impermeable membrane, i.e., a solid or gel ion conductor, thereby allowing the transport of ions. In some embodiments, the separator 130 is a porous polymeric membrane infused with a liquid electrolyte that allows for the transport of ions back and forth between the electroactive materials of the positive electrode 140 and negative electrode 150 while preventing the transfer of electrons. In some embodiments, the separator 130 is a microporous membrane that prevents particles that form the positive and negative electrode compositions from crossing the membrane. For example, the membrane material can be selected from polyethylene oxide (PEO) polymers in which lithium salts are synthesized to provide lithium conductivity or Nation™ membranes, which are proton conductors. For example, PEO-based electrolytes can be used as membranes that are pinhole-free, solid ionic conductors, and can be optionally stabilized by other membranes such as glass fiber separators as support layers. PEO can also be used as a slurry stabilizer, dispersant, etc. in positive or negative redox compositions. PEO is stable in contact with typical alkyl carbonate-based electrolytes. This can be particularly useful in phosphate-based cell chemistries with cell potentials of the positive electrode less than about 3.6 V with respect to Li metal. The operating temperature of the redox cell can be increased as needed to improve the ionic conductivity of the membrane.

[0047]

[0050] The cathode 140 can be a semi-solid stationary cathode or a semi-solid flowable cathode, for example of the type used in redox flow cells. The cathode 140 can include an active material, such as a lithium-containing compound, as described in more detail below. The cathode 140 can also include a conductive material, such as, for example, graphite, carbon powder, pyrolytic carbon, carbon black, carbon fiber, carbon microfiber, carbon nanotubes (CNTs), single-wall CNTs, multi-wall CNTs, fullerene carbon including "buckyballs," graphene sheets and / or aggregates of graphene sheets, any other conductive material, alloy, or combination thereof. The cathode 140 can also include a non-aqueous liquid electrolyte, as described in more detail below.

[0048]

[0051] In some embodiments, the semi-solid cathode 140 can include about 20% to about 75% by volume of active material, about 0.5% to about 25% by volume of conductive material, and about 25% to about 70% by volume of electrolyte. In some embodiments, the semi-solid cathode 140 can include about 60% to about 80% by weight of active material, about 1% to about 6% by weight of conductive material, and about 20% to about 40% by weight of non-aqueous liquid electrolyte.

[0049]

[0052] In some embodiments, the thickness t of the positive electrode 140 1 is the thickness t of the negative electrode 150 2 In some embodiments, the thickness t of the positive electrode 140 can be in the range of about 2 to about 6 times. 1 is the thickness t of the negative electrode 150 2 In some embodiments, the thickness t of the positive electrode 140 can be about twice as large as the thickness t 1 is the thickness t of the negative electrode 150 2 In some embodiments, the thickness t of the positive electrode 140 can be about three times as large as the thickness t 1 is the thickness t of the negative electrode 150 2 In some embodiments, the thickness t of the positive electrode 140 can be about four times as large as the thickness t 1 is the thickness t of the negative electrode 150 2In some embodiments, the thickness t of the positive electrode 140 can be about 5 times the thickness t 1 is the thickness t of the negative electrode 150 2 It can be about six times larger.

[0050]

[0053] The anode 150 can be a conventional anode formed, for example, by a conventional coating and calendaring process. In some embodiments, the anode 150 can be a semi-solid stationary anode. In some embodiments, the anode 150 can be a semi-solid flowable anode, for example, of the type used in redox flow cells. The anode 150 is a high capacity anode that includes a high capacity active material, for example, silicon, bismuth, boron, gallium, indium, zinc, tin, antimony, aluminum, titanium oxide, molybdenum, germanium, manganese, niobium, vanadium, tantalum, iron, copper, chromium, nickel, cobalt, zirconium, yttrium, molybdenum oxide, germanium oxide, silicon oxide, silicon carbide, any other high capacity material or alloys thereof, or any combination thereof.

[0051]

[0054] Anode 150 can also include a carbonaceous material, such as, for example, graphite, carbon powder, pyrolytic carbon, carbon black, carbon fibers, carbon microfibers, carbon nanotubes (CNTs), single-walled CNTs, multi-walled CNTs, fullerene carbon including "buckyballs," graphene sheets, and / or aggregates of graphene sheets, any other carbonaceous material, or combinations thereof. In some embodiments, anode 150 can also include a non-aqueous liquid electrolyte, as described in more detail below.

[0052]

[0055] In some embodiments, the thickness t of the negative electrode 150 2 is the thickness of the positive electrode 140 1 In some embodiments, the thickness t of the negative electrode 150 can be about 20 to 25% of the thickness t 2is about 30 μm to about 600 μm, about 40 μm to about 600 μm, about 50 μm to about 600 μm, about 70 μm to about 600 μm, about 100 μm to about 600 μm, about 150 μm to about 600 μm, about 200 μm to about 600 μm, about 50 μm to about 500 μm, about 100 μm to about 500 μm, about 150 μm to about 500 μm, about It can be within the range of 200 μm to about 500 μm, about 100 μm to about 400 μm, about 150 μm to about 400 μm, about 200 μm to about 400 μm, about 100 μm to about 300 μm, about 150 μm to about 300 μm, about 200 μm to about 300 μm, about 30 μm to about 200 μm, about 40 μm to about 200 μm, about 50 μm to about 200 μm, about 60 μm to about 200 μm, about 70 μm to about 200 μm, about 100 μm to about 200 μm, about 150 μm to about 200 μm, about 200 μm, or about 300 μm.

[0053]

[0056] In some embodiments, both the positive electrode 140 and the negative electrode 150 can comprise a semi-solid suspension. In such embodiments, the positive electrode 140 and the negative electrode 150 can comprise an active material and optionally a conductive material in the form of particulates suspended in a non-aqueous liquid electrolyte. In some embodiments, the particles of the positive electrode 140 and / or the negative electrode 150 have an effective diameter of at least about 1 μm. In some embodiments, the particles of the positive electrode 140 and / or the negative electrode 150 have an effective diameter of about 1 μm to about 10 μm. In other embodiments, the particles of the positive electrode 140 and / or the negative electrode 150 have an effective diameter of at least about 10 μm or more.

[0054]

[0057] In some embodiments, a redox mediator is used to improve charge transfer within the semi-solid suspension. In some embodiments, the redox mediator is Fe 2+ Or V 2+ , V 3+ , or V 4+ In some embodiments, the redox mediator is ferrocene.

[0055]

[0058] In some embodiments, the conductive particles have shapes that may include spheres, platelets, or rods to optimize the packing fraction of the solids, increase the net electronic conductivity of the semi-solid, and improve the rheological behavior of the semi-solid. Low aspect or substantially equiaxed particles tend to flow well but have low packing density.

[0056]

[0059] In some embodiments, the particles have multiple sizes to increase the packing fraction by filling the interstices of the larger particles with smaller particles. In particular, the particle size distribution can be bimodal, with the average particle size of the larger particle mode being at least 5 times larger than the average particle size of the smaller particle mode. Mixing the larger and smaller particles improves the flow of material during cell loading and increases the solid volume fraction and packing density in the loaded cells.

[0057]

[0060] In some embodiments, the properties of the semi-solid suspension of the positive electrode 140 and / or negative electrode 150 can be modified before and after loading of the negative and positive electroactive zones to facilitate flow during loading and packing density within the loaded cell.

[0058]

[0061] In some embodiments, the particle suspension is initially stabilized by interparticle steric repulsion arising from surfactant molecules. After the particle suspension is loaded into the positive and / or negative electroactive zones, chemical or thermal treatments can be used to disrupt or evaporate these surface molecules, facilitating densification. In some embodiments, the repulsion of the suspension is intermittently modified during loading.

[0059]

[0062] For example, the particle suspension can be initially stabilized by interparticle electrostatic double layer repulsion to reduce viscosity. This repulsion reduces interparticle attraction and reduces aggregation. After the particle suspension is loaded into the positive and / or negative electroactive zones, the surface of the particles can be further modified to reduce interparticle repulsion, thereby promoting particle attraction and packing. For example, to generate increased solid fractional loading after loading of the electroactive zones, an ionic solution such as a salt solution can be added to the suspension to reduce repulsion and promote aggregation and densification. In some embodiments, salt is added intermittently during suspension loading to increase density within incremental layers.

[0060]

[0063] In some embodiments, the positive and / or negative electroactive zones are loaded with a particle suspension stabilized by interparticle repulsion induced by electrostatic double layers or short-range repulsion by the addition of surfactants or dispersants. After loading, the particle suspension is aggregated and densified by increasing the salt concentration of the suspension. In some embodiments, the salt added is a salt of the working ion for the battery (e.g., lithium salt for a lithium ion battery) and, once added, the liquid phase becomes an ion-conducting electrolyte (e.g., for a lithium rechargeable battery, this could be one or more alkyl carbonates or one or more ionic liquids). By increasing the salt concentration, the electrical double layers that cause interparticle repulsion "break down" and the particles flocculate, aggregate, coagulate, or otherwise densify due to attractive interactions. This allows the formation of battery electrodes from the suspension while it has low viscosity, for example by pouring, injecting, or pumping into positive and / or negative electroactive zones where a mesh-like electrode can be formed, and then the particles in the suspension can be solidified for improved electrical conductivity, increased packing density, and extended shelf life.

[0061]

[0064] In some embodiments, the semi-solid suspension of flowable positive electrode 140 and / or negative electrode 150 is rendered non-flowable by "immobilization." In some embodiments, immobilization may be performed by the action of photopolymerization. In some embodiments, immobilization is performed by the action of electromagnetic radiation having a wavelength that is transmitted by the unfilled positive and / or negative electroactive zones of the electrochemical cell 100. In some embodiments, one or more additives are added to the semi-solid suspension to aid in immobilization.

[0062]

[0065] In some embodiments, the pourable, flowable semi-solid of the positive electrode 140 and / or negative electrode 150 is rendered non-flowable by "plasticization." In some embodiments, the rheological properties of the pourable, flowable semi-solid suspension are modified by the addition of thinners, thickeners, and / or plasticizers. In some embodiments, these agents aid in promoting processability and maintaining uniformity of the semi-solid composition under flow conditions and the filling operation of the positive and negative electroactive zones. In some embodiments, one or more additives are added to the flowable semi-solid suspension to adjust its flow properties to address processing requirements.

[0063] semi-solid composition

[0066] The semi-solids of the positive electrode 140 in some embodiments and the negative electrode 150 in some embodiments provide a means to create a material that collectively functions as an ion storage / ion source, an electronic conductor, and an ion conductor in a single medium that operates as a working electrode.

[0064]

[0067] As described herein, the semi-solid ion storage redox composition of the positive electrode 140 and / or the negative electrode 150 can have a concentration of at least 10M of redox species when considered in moles per liter (molar concentration). In some embodiments, the semi-solid ion storage redox composition of the positive electrode 140 and / or the negative electrode 150 can have a concentration of at least 12M, at least 15M, or at least 20M. The electrochemically active material can be an ion storage material and / or any other compound or ion complex capable of undergoing a faradaic reaction to store energy. The electroactive material can also be a multi-layer material, including the above-mentioned redox active solids mixed with a non-redox active phase, including solid-liquid suspensions or liquid multi-layer mixtures, including micelles or emulsions with liquid ion storage material intimately mixed with a supporting liquid phase. Systems using various working ions include Li + , Na + , or other alkali ions are the working ions, and Ca 2+ , Mg 2+ , or Al 3+ In some cases, the working ion may be an alkaline earth working ion, such as ZnO, ZnO, or ZnO. In other ... ZnO, or ZnO. In other cases, the working ion may be an alkaline earth working ion, such as ZnO, ZnO,

[0065]

[0068] Systems that use both negative and positive ion storage materials are particularly advantageous because no additional electrochemical by-products are generated within the cell. Both the positive and negative electrode materials are insoluble in the electrolyte, and the electrolyte does not become contaminated with electrochemical composition products. In addition, systems that use both negative and positive ion storage materials are particularly advantageous when using non-aqueous electrochemical compositions.

[0066]

[0069] In some embodiments, the semi-solid ion storage redox composition comprises materials that have been proven to function in conventional solid-state lithium ion batteries. In some embodiments, the positive semi-solid electroactive material comprises a lithium positive electroactive material, where lithium cations are shuttled between the negative and positive electrodes and intercalated within solid host particles that are suspended in a liquid electrolyte.

[0067]

[0070] In some embodiments, at least one of the semi-solid cathode 140 and / or anode 150 comprises a condensed ion-storage liquid of a redox active compound, which may be organic or inorganic, including but not limited to lithium metal, sodium metal, lithium metal alloys, gallium and indium alloys with or without dissolved lithium, molten transition metal chlorides, thionyl chloride, etc., or redox polymers and organics that may be liquid under the operating conditions of the battery. Such liquid forms may also be diluted or mixed with other non-redox active liquids that are diluents or solvents, including mixing with such diluents to form a low melting point liquid phase. In some embodiments, the redox active component may comprise at least 10% by weight of the total weight of the electrolyte. In other embodiments, the redox active component may comprise approximately 10% to 25% by weight of the total weight of the electrolyte. In some embodiments, the redox active component may comprise at least 25% or more by weight of the total weight of the electrolyte.

[0068]

[0071] In some embodiments, the redox-active electrode material comprises an organic redox compound that stores the working ion of interest at a potential useful for either the positive or negative electrode of the battery, whether used in a semi-solid or condensed liquid form as defined above. Such organic redox-active storage materials include "p"-doped conductive polymers such as polyaniline or polyacetylene-based materials, polynitroxide or organic radical electrodes (such as those described in H. Nishide et al., Electrochim. Acta, 50, 827-831 (2004) and K. Nakahara et al., Chem. Phys. Lett., 359, 351-354 (2002)), carbonyl-based organics, and Li 2 C 6 O 6 , Li 2 C 8 H 4 O 4 , and Li 2 C 6 H 4 O 4 (see, for example, M. Armand et al., Nature Materials, DOI: 10.1038 / nmat2372), as well as organosulfur compounds.

[0069]

[0072] In some embodiments, electronically insulating organic redox compounds are used. In some cases, the redox compounds are in a condensed liquid phase, such as an electronically insulating liquid or a flowable polymer. In such cases, the redox active slurry may or may not include an additional carrier liquid. Additives can be combined with the condensed phase liquid redox compounds to increase electronic conductivity. In some embodiments, such electronically insulating organic redox compounds are made electrochemically active by mixing or blending with particulates of electronically conducting materials, such as metals, metal carbides, metal nitrides, metal oxides, and solid inorganic conducting materials, including, but not limited to, metal allotropes, including carbon black, graphitic carbon, carbon fiber, carbon microfiber, vapor grown carbon fiber (VGCF), fullerene carbons, including "buckyballs", carbon nanotubes (CNTs), multi-walled carbon nanotubes (MWNTs), single-walled carbon nanotubes (SWNTs), graphene sheets or aggregates of graphene sheets, and materials containing fullerene fragments.

[0070]

[0073] In some embodiments, such electronically insulating organic redox compounds are made electronically active by blending or admixing with polyaniline or polyacetine based conductive polymers or electronically conductive polymers including, but not limited to, poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole, polythiophene, poly(p-phenylene), poly(triphenylene), polyazulene, polyfluorene, polynaphthalene, polyanthracene, polyfuran, polycarbazole, tetrathiafulvalene substituted polystyrene, ferrocene substituted polyethylene, carbazole substituted polyethylene, polyoxyphenazine, polyacene, or poly(heteroacene). The conductive additive forms a conductive framework within the insulating liquid redox compound that significantly increases the electrical conductivity of the composition. In some embodiments, the conductive additive forms a leaching path to the current collector. In some embodiments, the redox active electrode material comprises a sol or gel, including, for example, a metal oxide sol or gel produced by hydrolysis of a metal alkoxide, among other methods commonly known as the "sol-gel process." V x O y Among such redox-active sol-gel materials is vanadium oxide gel of the composition:

[0071]

[0074] Other suitable positive active materials for use in the positive electrode 140 include solid state compounds known to those skilled in the art for use in NiMH (nickel metal hydride) or nickel cadmium (NiCd) batteries. Yet other positive electrode compounds for Li storage are those used in carbon monofluoride batteries, commonly referred to as CFx, or with the approximate stoichiometry MF 2 Or MF 3where M includes, for example, Fe, Bi, Ni, Co, Ti, or V. See, for example, H. Li, P. Balaya, and J. Maier, Li-Storage via Heterogeneous Reaction in Selected Binary Metal Fluorides and Oxides, Journal of The Electrochemical Society, 151

[11] A1878-A1885 (2004), M. Bervas, AN Mansour, W.-S. Woon, J. F. Al-Sharab, F. Badway, F. Cosandey, L. C. Klein, and G. G. Matucci, "Investigation of the Lithiation and Delithiation Conversion Mechanisms in a Bismuth Fluoride Nanocomposites", J. Electrochem. Soc., 153, A799 (2006), and I. Plitz, F. Badway, J. Al-Sharab, A. DuPasquier, F. Cosandey, and G. G. Matucci, "Structure and Electrochemistry of Carbon-Metal Fluoride Nanocomposites Fabricated by a Solid State Redox Conversion Reaction," J. Electrochem. Soc., 152, A307 (2005).

[0072]

[0075] As another example, single-walled carbon nanotubes (SWNTs), multi-walled carbon nanotubes (MWNTs), or fullerene carbon containing metal or semimetal nanowires can be used as the ion storage material. One example is silicon nanowires used as the high energy density storage material in the report High-performance lithium battery anodes using silicon nanowires, Nature Nanotechnology, published online December 16, 2007; doi:10.1038 / nnano.2007.411, by C.K. Chan, H. Peng, G. Liu, K. McIlwrath, X.F. Zhang, R.A. Huggins, and Y. Cui. In some embodiments, the electroactive material for the positive electrode 140 in the lithium system is α-NaFeO 2 (so-called "layered compounds") or orthorhombic LiMnO 2 The ordered rock salt compound LiMO, including those having the structure type or derivatives thereof differing in crystal symmetry, atomic arrangement, or partial substitution of metal or oxygen. 2 M includes at least one first row transition metal, but may include non-transition metals, including but not limited to Al, Ca, Mg, or Zr. Examples of such compounds include LiCoO 2 , Mg-doped LiCoO 2 , LiNiO 2 , Li(Ni,Co,Al)O 2 (known as "NCA"), and Li(Ni,Mn,Co)O 2 (known as "NMC"). Other series of exemplary cathode 140 electroactive materials include LiMn 2 O 4 and its derivatives, the so-called "laminated spinel nanocomposites" whose structures contain nanoscopic domains with ordered rocksalt and spinel arrangements, olivine LiMPO, where M contains one or more of Mn, Fe, Co, or Ni. 4 and their derivatives, LiVPO 4Partially fluorinated compounds such as F, other "polyanionic" compounds described below, as well as V 2 O 5 and V 6 O 11 Vanadium oxide containing V x O y These include those with spinel structures such as:

[0073]

[0076] In some embodiments, the electroactive material of the positive electrode 140 comprises a transition metal polyanion compound, for example, as described in U.S. Pat. No. 7,338,734. In some embodiments, the active material comprises an alkali metal transition metal oxide or phosphate, for example, the compound is x (M' 1-a M” a ) y (XD 4 ) z , A x (M' 1-a M” a ) y (DXD 4 ) z , or A x (M' 1-a M” a ) y (X 2 D 7 ) z x plus y(1-a) times one or more formal valences of M' plus ya times one or more formal valences of M" is XD 4 , X 2 D 7 , or DXD 4 z times the formal valence of the group, or a compound has (A 1-a M” a ) x M' y (XD 4 ) z , (A 1-a M” a ) x M' y (DXD 4 ) z (A 1-a M” a ) x M'y (X 2 D 7 ) z (1-a) x plus one or more formal valences of M″ times ax plus one or more formal valences of M′ times y is XD 4 , X 2 D 7 , or DXD 4 In this compound, A is at least one of an alkali metal and hydrogen, M' is a first row transition metal, X is at least one of phosphorus, sulfur, arsenic, molybdenum, and tungsten, M" is any of the metals of Groups IIA, IIIA, IVA, VA, VIA, VIIA, VIIIA, IB, IIB, IIIB, IVB, VB, and VIB, and D is at least one of oxygen, nitrogen, carbon, or a halogen. The positive electroactive material is the olivine structure compound LiMPO 4 where M is one or more of V, Cr, Mn, Fe, Co, and Ni, and the compound is optionally doped at Li, M, or O sites. Deficiencies at the Li sites are compensated for by metal or metalloid additions, and deficiencies at the O sites are compensated for by halogen additions. In some embodiments, the positive active material has an olivine structure and is (Li 1-x Z x )MPO 4 wherein M is one or more of V, Cr, Mn, Fe, Co, and Ni; Z is a non-alkali metal dopant such as one or more of Ti, Zr, Nb, Al, or Mg; and x is in the range of 0.005 to 0.05.

[0074]

[0077] In other embodiments, the lithium transition metal phosphate material is Li 1-x-z M 1+z PO 4has the overall composition where M comprises at least one Group 1 transition metal selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, and Ni, where x is from 0 to 1 and z can be positive or negative. M includes Fe and z is between about 0.15 and 0.15. This material can exhibit a solid solution over the composition range of 0 < x < 0.15, or this material can exhibit a stable solid solution over the composition range of x between 0 and at least about 0.05, or this material can exhibit a stable solid solution over the composition range of x between 0 and at least about 0.07 at room temperature (22 - 25 °C). Also, this material can exhibit a solid solution in a lithium-deficient situation, for example, in the situation where x ≥ 0.8 or x ≥ 0.9 or x ≥ 0.95.

[0075]

[0078] In some embodiments, the redox-active electrode material includes a metal salt that accumulates alkali ions by undergoing a substitution or conversion reaction. Examples of such compounds typically include metal oxides such as CoO, Co 3 O 4 , NiO, CuO, MnO, etc., which, when reacted with Li, undergo a substitution or conversion reaction to form a mixture of Li 2 O and a metal component in a more reduced oxide form or in the form of a metal. Other examples include CuF 2 , FeF 2 , FeF 3 , BiF 3 , CoF 2 , and NiF 2and other metal fluorides, which undergo a substitution or conversion reaction to form LiF and a reduced metal component. Such fluorides can be used as positive electrodes in lithium batteries. In other embodiments, the redox active electrode material includes carbon monofluoride or a derivative thereof. In some embodiments, the material that has undergone the substitution or conversion reaction is in the form of a particulate having an average dimension of 100 nanometers or less. In some embodiments, the material that has undergone the substitution or conversion reaction includes a nanocomposite of an active material mixed with an inert host, including, but not limited to, a conductive and relatively ductile compound such as carbon, or a metal, or a metal sulfide. Also, FeS 2 and FeF 3 It can also be used as an inexpensive, electronically conductive active material in non-aqueous or aqueous lithium-ion systems.

[0076]

[0079] In some embodiments, the working ion is Li + , Na + , H + , Mg 2+ , Al 3+ , or Ca 2+ is selected from the group consisting of:

[0077]

[0080] In some embodiments, the working ion is Li + Or Na + is selected from the group consisting of:

[0078]

[0081] In some embodiments, the semi-solid ion-storing redox composition comprises a solid that includes an ion-storing compound.

[0079]

[0082] In some embodiments, the ions are protons or hydroxide ions, and ion storage compounds include those used in nickel cadmium or nickel metal hydride batteries.

[0080]

[0083] In some embodiments, the ion is lithium and the ion storage compound is CuF 2 , FeF 2 , FeF3 , BiF 3 , CoF 2 , and NiF 2 and the like.

[0081]

[0084] In some embodiments, the ion is lithium and the ion storage compound is CoO, Co 3 O 4 , NiO, CuO, MnO and other metal oxides.

[0082]

[0085] In some embodiments, the ion is lithium and the ion storage compound is (Li 1-x Z x )MPO 4 where M is one or more of V, Cr, Mn, Fe, Co, and Ni, Z is a non-alkali metal dopant such as one or more of Ti, Zr, Nb, Al, or Mg, and x is in the range of 0.005 to 0.05.

[0083]

[0086] In some embodiments, the ion is lithium and the ion storage compound is LiMPO 4 where M is one or more of V, Cr, Mn, Fe, Co, and Ni, and the compound is optionally doped at Li, M, or O.

[0084]

[0087] In some embodiments, the ion is lithium and the ion storage compound is A x (M' 1-a M” a ) y (XD 4 ) z , A x (M' 1-a M” a ) y (DXD 4 ) z , and A x (M' 1-a M” a )y (X 2 D 7 ) z wherein x plus y(1-a) times one or more formal valences of M' plus ya times one or more formal valences of M" is selected from the group consisting of XD 4 , X 2 D 7 , or DXD 4 A is equal to z times the formal valence of the group, A is at least one of an alkali metal and hydrogen, M' is a first row transition metal, X is at least one of phosphorus, sulfur, arsenic, molybdenum, and tungsten, M" is any of the metals of Groups IIA, IIIA, IVA, VA, VIA, VIIA, VIIIA, IB, IIB, IIIB, IVB, VB, and VIB, and D is at least one of oxygen, nitrogen, carbon, or halogen.

[0085]

[0088] In some embodiments, the ion is lithium and the ion storage compound is (A 1- aM” a ) x M' y (XD 4 ) z , (A 1-a M” a ) x M' y (DXD 4 ) z , and (A 1-a M” a ) x M' y (X 2 D 7 ) z wherein (1-a) x plus ax times the quantity of one or more formal valences of M″ plus y times the quantity of one or more formal valences of M′ is XD 4 , X 2 D 7 , or DXD 4A is equal to z times the formal valence of the group, A is at least one of an alkali metal and hydrogen, M' is a first row transition metal, X is at least one of phosphorus, sulfur, arsenic, molybdenum, and tungsten, M" is any of the metals of Groups IIA, IIIA, IVA, VA, VIA, VIIA, VIIIA, IB, IIB, IIIB, IVB, VB, and VIB, and D is at least one of oxygen, nitrogen, carbon, or halogen.

[0086]

[0089] In some embodiments, the ion is lithium and the ion storage compound is α-NaFeO 2 and orthorhombic LiMnO 2 The ordered rock salt compound LiMO, including those having the structure type or derivatives thereof differing in crystal symmetry, atomic arrangement, or partial substitution of metal or oxygen. 2 where M comprises at least one first row transition metal, but may include non-transition metals, including, but not limited to, Al, Ca, Mg, or Zr.

[0087]

[0090] In some embodiments, the semi-solid ion-storing redox composition comprises a solid that includes amorphous carbon, disordered carbon, graphitic carbon, or metal-coated or metal decorated carbon.

[0088]

[0091] In some embodiments, the semi-solid ion-storing redox composition can include solids that include nanostructures, for example, nanowires, nanorods, and nanotetrapods.

[0089]

[0092] In some embodiments, the semi-solid ion-storing redox composition comprises a solid that includes an organic redox compound.

[0090]

[0093] In some embodiments, the positive electrode is α-NaFeO 2 and orthorhombic LiMnO 2The ordered rock salt compound LiMO, including those having the structure type or derivatives thereof differing in crystal symmetry, atomic arrangement, or partial substitution of metal or oxygen. 2 where M comprises at least one first row transition metal, but may include a non-transition metal, including but not limited to Al, Ca, Mg, or Zr. The negative electrode may comprise a semi-solid ion-storing redox composition comprising a solid selected from the group consisting of amorphous carbon, disordered carbon, graphitic carbon, or metal-coated or metal-decorated carbon.

[0091]

[0094] In some embodiments, the positive electrode is A x (M' 1-a M” a ) y (XD 4 ) z , A x (M' 1-a M” a ) y (DXD 4 ) z , and A x (M' 1-a M” a ) y (X 2 D 7 ) z wherein x plus y times one or more formal valences of M' plus ya times one or more formal valences of M" is XD 4 , X 2 D 7 , or DXD 4group, A is at least one of an alkali metal and hydrogen, M' is a first row transition metal, X is at least one of phosphorus, sulfur, arsenic, molybdenum, and tungsten, M" is any of the metals in Groups IIA, IIIA, IVA, VA, VIA, VIIA, VIIIA, IB, IIB, IIIB, IVB, VB, and VIB, D is at least one of oxygen, nitrogen, carbon, or a halogen, and the negative electrode comprises a flowable semi-solid ion-storing redox composition comprising a solid selected from the group consisting of amorphous carbon, disordered carbon, graphitic carbon, or metal-coated or metal-decorated carbon.

[0092]

[0095] In some embodiments, the positive electrode can include a flowable semi-solid ion-storing redox composition that includes a compound having a spinel structure.

[0093]

[0096] In some embodiments, the positive electrode is LiMn 2 O 4 and derivatives thereof, layered spinel nanocomposites whose structures include nanoscopic domains with ordered rocksalt and spinel sequences, so-called "high voltage spinels" with potentials vs. Li / Li+ exceeding 4.3 V, including but not limited to LiNi0.5Mn1.5O4, olivine LiMPO, where M includes one or more of Mn, Fe, Co, or Ni. 4 and their derivatives, LiVPO 4 Partially fluorinated compounds such as F, other "polyanionic" compounds, and V 2 O 5 and V 6 O 11 Vanadium oxide containing V x O y The present invention relates to a flowable semi-solid ion-storing redox composition comprising a compound selected from the group consisting of:

[0094]

[0097] In some embodiments, the semi-solid battery is a lithium battery and the compound of the anode 150 includes graphite, graphitic or non-graphitic carbon, amorphous carbon, mesocarbon microbeads, boron carbon alloys, hard or disordered carbon, lithium titanate spinel, or a solid metal or metal alloy or metalloid or metalloid alloy that reacts with lithium to form an intermetallic compound, such as Si, Ge, Sn, Bi, Zn, Ag, Al, any other suitable metal alloy, metalloid alloy, or combination thereof. In particular, these metals, metal alloys, or metalloids include, for example, silicon, bismuth, barium, gallium, indium, zinc, tin, antimony, aluminum, gold, titanium oxide, molybdenum, germanium, manganese, niobium, vanadium, tantalum, iron, copper, chromium, nickel, cobalt, zirconium, yttrium, molybdenum oxide, germanium oxide, silicon oxide, silicon carbide, or LiAl, Li 9 Al 4 , Li 3 Al, LiZn, LiAg, Li 10 Ag 3 , Li 5 B 4 , Li 7 B 6 , Li 12 S 7 , Li 21 S 8 , Li 13 S 4 , Li 21 S 5 , Li 5 Sn 2 , Li 13 Sn 5 , Li 7 Sn 2 , Li 22 Sn 5 , Li 2 Sb, Li 3 Sb, LiBi, or Li 3The negative electrode 150 may be selected from the group having a large capacity for inserting lithium, such as a lithiated metal or metal alloy, including compounds such as Bi, or an amorphous metal alloy of lithiated or non-lithiated composition, any other high capacity material or alloy thereof, or any other combination thereof. In some embodiments, the high capacity material in the negative electrode 150 may result in the negative electrode 150 having a capacity in the range of about 700 mAh / g to about 1200 mAh / g.

[0095]

[0098] In some embodiments, the electrochemical function of the semi-solid redox cell is improved by mixing or blending the particles of the positive electrode 140 and / or the negative electrode 150 with fine particles of electronically conductive materials such as metals, metal carbides, metal nitrides, metal oxides, and solid inorganic conductive materials including, but not limited to, materials containing metal allotropes including carbon black, graphitic carbon, carbon fiber, carbon microfiber, vapor-grown carbon fiber (VGCF), fullerene carbon including "buckyballs", carbon nanotubes (CNTs), multi-walled carbon nanotubes (MWNTs), single-walled carbon nanotubes (SWNTs), graphene sheets or aggregates of graphene sheets, and fullerene fragments. In some embodiments, such electronically insulating organic redox compounds are made electronically active by blending or admixing with polyaniline or polyacetine based conductive polymers, or electronically conductive polymers including, but not limited to, poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole, polythiophene, poly(p-phenylene), poly(triphenylene), polyazulene, polyfluorene, polynaphthalene, polyanthracene, polyfuran, polycarbazole, tetrathiafulvalene substituted polystyrene, ferrocene substituted polyethylene, carbazole substituted polyethylene, polyoxyphenazine, polyacene, or poly(heteroacene). In some embodiments, the resulting positive or negative electrode blend has a molecular weight of at least about 10 -6 In other embodiments, the mixture has an electronic conductivity of approximately 10 -6 S / cm~10 -3In other embodiments, the mixture has an electronic conductivity of at least about 10 -5 S / cm or at least 10 -4 S / cm, at least about 10 -3 S / cm, at least about 10 -2 It has electronic conductivity of more than S / cm.

[0096]

[0099] In some embodiments, the particles included in the semi-solid anode or cathode can be configured to have a partial or complete conductive coating.

[0097]

[0100] In some embodiments, the semi-solid ion-storing redox composition includes an ion-storing solid coated with a conductive coating. In some embodiments, the conductive coating has a higher electronic conductivity than the solid. In some embodiments, the solid is graphite and the conductive coating is a metal, metal carbide, metal oxide, metal nitride, or carbon. In some embodiments, the metal is copper.

[0098]

[0101] In some embodiments, the solids of the semi-solid ion storage material are coated with a metal that is redox inactive at the operating conditions of the redox energy storage device. In some embodiments, the solids of the semi-solid ion storage material are coated with copper to increase the conductivity of the storage material particles, to increase the net conductivity of the semi-solid, and / or to facilitate charge transfer between the energy storage particles and the conductive additive. In some embodiments, the storage material particles are coated with about 1.5% metallic copper by weight. In some embodiments, the storage material particles are coated with about 3.0% metallic copper by weight. In some embodiments, the storage material particles are coated with about 8.5% metallic copper by weight. In some embodiments, the storage material particles are coated with about 10.0% metallic copper by weight. In some embodiments, the storage material particles are coated with about 15.0% metallic copper by weight. In some embodiments, the storage material particles are coated with about 20.0% metallic copper by weight.

[0099]

[0102] In some embodiments, a conductive coating is placed on particles of the positive electrode 140 and / or negative electrode 150 by chemical precipitation of a conductive element followed by drying and / or calcination.

[0100]

[0103] In some embodiments, the conductive coating is placed on particles of the positive electrode 140 and / or negative electrode 150 by electroplating (eg, in a fluidized bed).

[0101]

[0104] In some embodiments, a conductive coating is placed on particles of the positive electrode 140 and / or negative electrode 150 by co-sintering with a conductive compound and then grinding.

[0102]

[0105] In some embodiments, the electrochemically-active particles have a continuous intragranular conductive material or are embedded within a conductive matrix.

[0103]

[0106] In some embodiments, the conductive coating and intra-particulate conductive network are produced by multi-component spray drying of particles of the semi-solid positive electrode 140 and / or negative electrode 150 and conductive material particulates.

[0104]

[0107] In some embodiments, the semi-solid composition also includes a conductive polymer that provides an electronically conductive element. In some embodiments, the conductive polymer is one or more of polyacetylene, polyaniline, polythiophene, polypyrrole, poly(p-phenylene), poly(triphenylene), polyazulene, polyfluorene, polynaphthalene, polyanthracene, polyfuran, polycarbazole, polyacene, poly(heteroacene). In some embodiments, the conductive polymer is a compound that reacts in situ to form a conductive polymer on the surface of the active material particles. In some embodiments, the compound can be 2-hexylthiophene or 3-hexylthiophene, which oxidizes during charging of the battery to form a conductive polymer coating on the solid particles in the positive electrode semi-solid suspension. In other embodiments, the redox active material can be embedded in a conductive matrix. The redox active material can coat the outer and inner boundary surfaces in the aggregated or agglomerated particulates of the conductive material. In some embodiments, the redox active material and the conductive material can be two components of a composite particulate. Without being bound by any theory or mode of operation, such a coating can sink the redox active particles and help prevent unwanted reactions with the carrier liquid or electrolyte, and thus can function as a synthetic solid electrolyte interphase (SEI) layer.

[0105]

[0108] In some embodiments, pyrite (FeS) is used as the essentially electronically conductive ion storage compound. 2 In some embodiments, inexpensive iron compounds such as Li + It is.

[0106]

[0109] In some embodiments, a redox mediator is added to the semi-solid to improve the rate of charge transfer in the semi-solid electrode. In some embodiments, the redox mediator is ferrocene or a ferrocene-containing polymer. In some embodiments, the redox mediator is one or more of tetrathiafulvalene-substituted polystyrene, ferrocene-substituted polyethylene, and carbazole-substituted polyethylene.

[0107]

[0110] In some embodiments, the surface conductivity or charge transfer resistance of the current collector 110 / 120 in the semi-solid battery is increased by coating the current collector surface with a conductive material. Such a layer can also function as a synthetic SEI layer. Non-limiting examples of conductive coating materials include carbon, metal, metal carbide, metal nitride, metal oxide, or conductive polymer. In some embodiments, the conductive polymer includes, but is not limited to, polyaniline or polyacetylene-based conductive polymers, or poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole, polythiophene, poly(p-phenylene), poly(triphenylene), polyazulene, polyfluorene, polynaphthalene, polyanthracene, polyfuran, polycarbazole, tetrathiafulvalene-substituted polystyrene, ferrocene-substituted polyethylene, carbazole-substituted polyethylene, polyoxyphenazine, polyacene, or poly(heteroacene). In some embodiments, the conductive polymer is a compound that reacts in situ to form a conductive polymer on the surface of the current collector. In some embodiments, the compound is 2-hexylthiophene, which oxidizes at high potential to form a conductive polymer coating on the current collector. In some embodiments, the current collector is coated with a metal that is redox inactive at the operating conditions of the redox energy storage device.

[0108]

[0111] Semi-solid redox compositions may contain various additives to improve the performance of the redox cell. The liquid phase of the semi-solid in such cases will contain a solvent in which the electrolyte salt is dissolved, and binders, thickeners, or other additives may be added to improve stability, reduce foaming, improve SEI formation on the negative electrode particles, etc. Examples of such additives include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), or alkyl cinnamates to provide a stable passivation layer on the negative electrode or a thin passivation layer on the oxide positive electrode, propane sultone (PS), propene sultone (PrS), or ethylene thiocarbonate as antigassing agents, biphenyl (BP), cyclohexylbenzene, or partially hydrogenated terphenyl as foaming / safety / positive electrode polymerization agents, or lithium bis(oxatrate)borate as a negative electrode passivation agent.

[0109]

[0112] In some embodiments, the semi-solid cathode 140 and / or anode 150 can include a non-aqueous liquid electrolyte, which can include a polar solvent, such as, for example, an alcohol or an aprotic organic solvent. A number of organic solvents have been proposed as components of Li-ion battery electrolytes, including, among others, the series of cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and their chlorinated or fluorinated derivatives, and the series of acyclic dialkyl carbonates such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dibutyl carbonate, butyl methyl carbonate, butyl ethyl carbonate, and butyl propyl carbonate. Other solvents that have been proposed as components of Li-ion battery electrolytes include y-butyrolactone, dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, diethyl ether, sulfolane, methylsulfolane, acetonitrile, propiononitrile, ethyl acetate, methyl propionate, ethyl propionate, dimethyl carbonate, tetraglyme, and the like. These non-aqueous solvents are typically used as multicomponent mixtures in which a salt is dissolved to provide ionic conductivity. Exemplary salts for providing lithium conductivity include LiClO 4 , LiPF 6 , LiBF 4 , LiTFSI, LiBETI, LiBOB, etc.

[0110]

[0113] In some embodiments, for example in the case of a redox flow cell battery, the incorporation of a water gettering compound in the active material suspension or in the storage tank or other plumbing of the system allows the semi-solid composition of the non-aqueous cathode 140 and / or anode 150 to absorb impurity water and convert it into acid (LiPF 6In the case of salts, the additive prevents the formation of acids (such as HF). Optionally, the additive is a basic oxide that neutralizes the acid. Such compounds include, but are not limited to, silica gel, calcium sulfate (e.g., the product known as Drierite), aluminum oxide, and aluminum hydroxide.

[0111]

[0114] In some embodiments, the positive electrode 140 can be a semi-solid positive electrode and the negative electrode 150 can be a conventional negative electrode, e.g., a solid negative electrode formed from a known calendaring process as is generally known in the art. In some embodiments, the positive electrode 140 can be a semi-solid positive electrode and the negative electrode 150 can also be a semi-solid negative electrode as described herein. In some embodiments, both the positive electrode 140 and the negative electrode 150 can be semi-solid flowable electrodes, e.g., for use in a redox flow cell.

[0112]

[0115] 2 shows a schematic diagram of an electrochemical cell 200 including a positive current collector 210, a negative current collector 220, and a separator 230 disposed between the positive current collector 210 and the negative current collector 220. Both the positive current collector 210 and the negative current collector have a thickness t 3 and the separator 230 has a thickness t 4 The thickness t 5 A positive electrode 240 having a thickness t 6 A negative electrode 250 having a negative charge carrier 240 is disposed between the negative current collector 220 and the separator 230.

[0113]

[0116] The positive and negative electrodes 240 and 250 of the electrochemical cell 200 can be formed using conventional coating and calendaring processes. For example, the positive and negative electrodes 240 and 250 can be fabricated by mixing an electrochemically active ion storage compound (active material), an electronically conductive additive, and a polymeric binder with a solvent to form a slurry, coating the slurry onto metal foil current collectors 210 and 220, and then calendering the coated current collectors at high pressure to increase density and control thickness of the finished electrodes. The finished electrodes are then cut / cut into sizes and / or shapes appropriate for the fabricated battery form factor. The cut electrode composites can then be co-wound or co-laminated with an intervening layer of separator 230 to construct a battery winding, i.e., "jelly roll" or "stack," and the windings are then placed into a metal can, flexible polymer pouch, or the like. The resulting electrochemical cell is then infiltrated with a liquid electrolyte in a carefully controlled environment.

[0114]

[0117] The negative electrode 250 can be a conventional negative electrode (e.g., carbon-based) such that the negative electrode 250 and the positive electrode 240 can have comparable capacities, e.g., about 150-200 mAh / g. Thus, the thickness t of the positive electrode 240 can be 5 and the thickness of the negative electrode 250 t 6 The thickness t of the separator 220 is substantially the same, for example, about 150 μm, and the capacitance of the negative electrode 240 and the positive electrode 250 are “matched.” 4 is typically the thickness t of the positive electrode 240 5 and the thickness t of the negative electrode 250 6 The current collector can be a metal foil having a thickness comparable to that of the separator, for example, about 20 μm.

[0115]

[0118] One significant disadvantage of conventional electrodes used in electrochemical cell 200 is the inability to increase the active material loading density to increase the capacity of the electrode, due in part to the manufacturing limitations of the coating / calendering process. Also, it is impractical to increase the electrode thickness beyond 150-200 μm in conventional electrochemical cells because (1) thicker electrodes made using conventional coating / calendering processes tend to delaminate from the current collector during high speed coating and rolling processes, and (2) thicker electrodes made using conventional coating / calendering processes have low conductivity, thereby dramatically increasing the cell impedance. To overcome these limitations, a series of cells are typically stacked to obtain the desired capacity. As a result of stacking the cells in this manner, a significant portion of the battery volume is occupied by inactive materials, i.e., separator 230 and current collectors 210 and 220. Thus, the ratio of active material to inactive material is low, which correlates to a significant reduction in energy density.

[0116]

[0119] For example, the thickness t of the current collectors 210 and 220 3 20 μm, and the thickness t 4 If the thickness t of the positive electrode 240 is also 20 μm, the total thickness of the inactive material will be 60 μm. 5 is 150 μm, and the thickness t 6 If the total active material thickness is also 150 μm, then the total active material thickness will be 300 μm. Thus, approximately 16% of the total thickness of electrochemical cell 200 is occupied by inactive material that does not contribute to the energy density and charge capacity of the battery.

[0117]

[0120] One option for providing higher energy capacity is by using a high-capacity active material, such as Si or Sn, in the negative electrode composition. Figure 3 shows a schematic diagram of a high-capacity electrochemical cell 300, including a positive current collector 310, a negative current collector 320, and a separator 330 disposed between the positive current collector 310 and the negative current collector 320. Both the positive current collector 310 and the negative current collector 320 have a thickness t 7 and the separator 330 has a thickness t8 The thickness t 9 A positive electrode 340 having a thickness t 10 A high capacity negative electrode 350 having a negative current collector 320 and a separator 330 is disposed between the negative current collector 320 and the separator 330.

[0118]

[0121] The cathode 340 can be any conventional cathode that uses a binder. The cathode 340 can be fabricated using conventional methods, such as those described in connection with FIG. 2. The thickness t of the conventional cathode 340 is 9 The thickness t of the negative electrode 350 can be, for example, about 150 μm and can have a capacity of, for example, about 150-200 mAh / g. The negative electrode 350 is a high capacity negative electrode that includes a high capacity material, for example, Si or Sn, and can have any composition described herein. The negative electrode 350 can have a capacity of, for example, about 700-1200 mAh / g. The negative electrode 350 has a significantly larger capacity than a conventional negative electrode, for example, the negative electrode 250, but the capacity of the negative electrode 350 must match the capacity of the positive electrode 340. Conventional positive electrodes 340 used in the electrochemical cell 300 cannot have a thickness t of greater than about 150-200 μm due to limitations described herein. 9 For example, a high-capacity negative electrode 350 needs to have a thickness t of about 30 to 50 μm to have a capacity matching that of the positive electrode 340. 10 Coatings on the order of 30-50 μm begin to approach the thickness level of a single graphite particle and are therefore manufactured using expensive fabrication processes, such as atomic layer deposition, vapor deposition, sputtering, etc. This limitation prevents full utilization of the potential energy capacity achievable in high capacity anodes 350.

[0119]

[0122] As described in connection with electrochemical cell 200, a series of individual cells 300 can be stacked together to increase the capacity of the battery. Although the capacities of electrochemical cells 200 and 300 are substantially equivalent, anode 350 is much thinner than anode 250, allowing more individual cells 300 to fit into a "stack" of a given form factor. However, a significant percentage of the completed battery is still occupied by inactive material. For example, the thickness t of current collectors 310 and 320 7 is the same as that of the current collectors 210 and 220 (i.e., 20 μm each), and the thickness t 8 is the same as that of the separator 230 (i.e., 20 μm), which represents a total thickness of the inactive material of 60 μm. 9 is the same as the positive electrode 240 (i.e., 150 μm), and the thickness t 10 is 50 μm, the total thickness of the active material will be 200 μm. Thus, almost 23% of the total thickness of the electrochemical cell 300 is occupied by inactive material that does not contribute to the energy density and charge capacity of the battery. Although the capacity of the completed battery using the electrochemical cell 300 in this example would be greater than that of the completed battery using the electrochemical cell 200, the thinner anode 350 allows more cells 300 to be packed into the same form factor, so a higher proportion of the completed battery is made of material that does not contribute to the charge capacity of the battery (23% vs. 16%), thus reducing its energy density. In other words, the high-capacity anode 350 allows more electrochemical cells 300 to be stacked in the battery compared to the conventional anode 250 to obtain a higher capacity battery, but also a higher proportion of inactive material, which negates some of this benefit.

[0120]

[0123] As described herein, increasing the thickness of the positive electrode and / or increasing the loading of active material within the positive electrode are two ways in which the benefits of a high-capacity negative electrode can be utilized. While these are not feasible options for conventional positive electrodes for the reasons discussed above, various embodiments of semi-solid positive electrodes described herein can be thicker than the maximum thickness of 200 μm achievable with conventional positive electrodes, and the loading density can be up to five times higher than conventional positive electrodes. FIG. 4 shows a schematic diagram of an electrochemical cell 400 including a positive current collector 410, a negative current collector 420, and a separator 430 disposed between the positive current collector 410 and the negative current collector 420. Both the positive current collector 410 and the negative current collector 420 have a thickness t 11 and the separator 430 has a thickness t 12 The thickness t 13 A semi-solid positive electrode 440 having a thickness t 14 A high capacity negative electrode 450 having a negative current collector 420 and a separator 430 is disposed between the negative current collector 420 and the separator 430.

[0121]

[0124] Anode 450 is a high-capacity anode that can be formed using the conventional method described above in connection with FIG. 2 or any other conventional method. In some embodiments, anode 450 can be a stationary semi-solid or flowable semi-solid anode as described herein. Cathode 440 is a semi-solid cathode that can be a stationary semi-solid or flowable semi-solid cathode as described herein. In some embodiments, the semi-solid cathode is substantially free of binders typically used in conventional calendared electrodes. In contrast to conventional cathodes, e.g., cathodes 240 and 340, semi-solid cathode 440 can be thicker than 200 μm, such as thicker than 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, or 1500 μm, up to 2000 μm or more, as described herein. In some embodiments, the positive electrode can be at least about 2, 3, 4, 5, or even 6 times the thickness of the negative electrode. Semi-solid positive electrode 440 can also be formulated to have up to five times the loading density of a conventional positive electrode. Thicker positive electrodes 440 and greater loading densities can be achieved with semi-solid positive electrode 440 without the negative consequences associated with thicker conventional electrodes.

[0122]

[0125] Thickness of semi-solid positive electrode 440 t 13 This allows the thickness t of the high-capacity negative electrode 450 to be substantially increased without compromising the thickness imposed by the limitations of conventional positive electrodes, e.g., positive electrodes 250 and 350. 14 Thus, the negative electrode 450 can be made thicker to match the capacity of the thicker positive electrode 450. For example, the negative electrode 450 can be made thicker, t, to a thickness of about 70 μm to about 200 μm using conventional coating / calendering manufacturing methods, or 600 μm or more when a semi-solid negative electrode is used as described herein. 14 may have the following structure:

[0123]

[0126] Thus, the semi-solid positive electrode 440 and high capacity negative electrode 450 of the electrochemical cell 400 formed using the formulations and methods described herein allow the maximum capacity provided by the high capacity material of the negative electrode 450 to be used in fewer stacks of electrochemical cells. In some embodiments, the semi-solid positive electrode 440 and the high capacity negative electrode 450 can be used to create a single electrochemical cell 400 without stacking. The ratio of active material to inactive material in the cell stack formed from the electrochemical cell 400 is much higher than that of the electrochemical cells 200 and 300 because no stacking is required or the number of stacks in a battery using the semi-solid positive electrode 440 is much less than the number of stacks required in a battery with a high capacity negative electrode and a conventional positive electrode, e.g., the electrochemical cell 300, or a battery with a conventional negative electrode and a conventional positive electrode, e.g., the electrochemical cell 200. Thus, most of the volume of the assembled battery is occupied by the active charge storage material, thereby increasing the overall charge capacity and energy density of the battery. For example, as shown in FIG. 4, the thickness t of the current collectors 410 and 420 is 0.01 mm. 11 is the same as that of the current collectors 310 and 320 (i.e., 20 μm each), and the thickness t 12 is the same as that of the separator 330 (i.e., 20 μm), which represents a total thickness of the inactive material of 60 μm. 13 The thickness of the large-capacity negative electrode is 500 μm, and the thickness t 14 is 150 μm, the total thickness of the active material will be 650 μm. Therefore, approximately 8.4% of the total thickness of the electrochemical cell 400 is occupied by inactive materials that do not contribute to the energy density and charge capacity of the battery. Since the proportion of inactive materials in the electrochemical cell 400 is approximately half that of the electrochemical cell 200 (16%) and approximately one-third that of the electrochemical cell 300 (23%), the electrochemical cell 400 has a much higher energy density than the other electrochemical cells 200 and 300 due to the full utilization of the large-capacity anode 450 and the higher input density of the semi-solid cathode 440.

[0124]

[0127] Furthermore, by using a semi-solid anode, the high capacity anode 450 can be thicker than 150 μm, and the semi-solid cathode 440 can be thicker than 500 μm to match the thicker high capacity anode 450, further reducing the proportion of inactive material that does not contribute to the battery's energy density and charge capacity. For example, the thickness t 14 is 600 μm, and the thickness t 13 If the thickness of the current collectors 410 and 420 and the separator 430 have the same thickness as above (i.e., 20 μm each), the percentage of inactive material is only approximately 2.2%. Thus, electrochemical cell 400 made with the above-described materials and methods has considerable commercial appeal, due in part to its increased energy density and decreased cost.

[0125]

[0128] While various embodiments of the present systems, methods, and apparatus have been described above, it should be understood that they are presented by way of example only and not by way of limitation. Where the above methods and steps show particular events occurring in a particular order, those skilled in the art having the benefit of the present invention will recognize that the ordering of certain steps may be altered and that such alterations are in accordance with variations of the present invention. Furthermore, some of the steps may not only be performed sequentially as described above, but may also be performed simultaneously in a parallel process when possible. While these embodiments have been shown and described in detail, it will be understood that various changes in form and detail are possible.

Claims

1. A positive electrode current collector; A negative electrode current collector; an ion-permeable membrane disposed between the positive electrode current collector and the negative electrode current collector, a first distance spaced from the positive electrode current collector and at least partially defining a positive electroactive zone; an ion permeable membrane spaced a second distance from the negative electrode current collector and at least partially defining a negative electroactive zone, the second distance being less than the first distance; a semi-solid positive electrode disposed within said positive electroactive zone and comprising a suspension of active material and conductive material in a non-aqueous liquid electrolyte; a negative electrode disposed within the negative electroactive zone; An electrochemical cell comprising:

2. The negative electrode comprises at least one high capacity negative electrode material selected from tin, silicon, antimony, aluminum, and titanium oxide; 2. The electrochemical cell of claim 1.

3. the first distance is at least about 250 μm; 2. The electrochemical cell of claim 1.

4. the first distance is at least about 300 μm; 4. The electrochemical cell of claim 3.

5. the first distance is at least about 350 μm; 5. The electrochemical cell of claim 4.

6. the first distance is at least about 400 μm; 6. The electrochemical cell of claim 5.

7. the first distance is within a range of about 250 μm to about 2000 μm; 2. The electrochemical cell of claim 1.

8. the first distance is within a range of about 350 μm to about 1000 μm; 8. The electrochemical cell of claim 7.

9. the first distance is within a range of about 450 μm to about 550 μm; 9. The electrochemical cell of claim 8.

10. the first distance is at least about 250 μm and the second distance is within a range of about 70 μm to about 120 μm; 2. The electrochemical cell of claim 1.

11. the first distance is at least about 400 μm; 11. The electrochemical cell of claim 10.

12. the negative electrode comprising a suspension of a negative electrode active material in a non-aqueous liquid electrolyte; 2. The electrochemical cell of claim 1.

13. a semi-solid positive electrode comprising a suspension of an active material and a conductive material in a non-aqueous liquid electrolyte, the semi-solid positive electrode having a capacity of about 150 mAh / g to about 200 mAh / g and a thickness in the range of about 250 μm to about 2000 μm; a negative electrode having a capacity in the range of about 700 mAh / g to about 1200 mAh / g and a thickness in the range of about 30 μm to about 600 μm; a separator disposed between the negative electrode and the semi-solid positive electrode; An electrochemical cell comprising:

14. the negative electrode comprises a lithium-alloying compound selected from tin, silicon, antimony, aluminum, and titanium oxide; 14. The electrochemical cell of claim 13.

15. the lithium alloying compound is silicon; 15. The electrochemical cell of claim 14.

16. the lithium alloying compound is tin; 15. The electrochemical cell of claim 14.

17. the thickness of the positive electrode is within a range of about 3 to about 6 times the thickness of the negative electrode; 14. The electrochemical cell of claim 13.

18. the negative electrode being a semi-solid negative electrode comprising a suspension of a negative electrode active material in a non-aqueous liquid electrolyte; 14. The electrochemical cell of claim 13.

19. A negative electrode; a semi-solid positive electrode material comprising about 60% to about 80% by weight of an active material, about 1% to about 6% by weight of a conductive material, and about 20% to about 40% by weight of a non-aqueous liquid electrolyte; a separator disposed between the negative electrode and the semi-solid positive electrode; Including, the thickness of the positive electrode is at least about twice the thickness of the negative electrode; Electrochemical cell.

20. the thickness of the positive electrode is at least about three times the thickness of the negative electrode; 20. The electrochemical cell of claim 19.

21. the thickness of the positive electrode is at least about four times the thickness of the negative electrode; 21. The electrochemical cell of claim 20.

22. the thickness of the positive electrode is at least about 5 times the thickness of the negative electrode; 22. The electrochemical cell of claim 21.

23. The negative electrode is a solid negative electrode formed on a negative electrode current collector.

20. The electrochemical cell of claim 19.

24. the negative electrode is a semi-solid negative electrode comprising about 50% to about 75% by volume of a carbonaceous active material, about 1% to about 10% by volume of a high energy capacity negative electrode material, about 0.5% to about 2% by volume of a conductive material, and about 20% to about 40% by volume of a non-aqueous liquid electrolyte; 20. The electrochemical cell of claim 19.

25. The high-capacity negative electrode material comprises at least one high-capacity negative electrode material selected from tin, silicon, antimony, aluminum, and titanium oxide; 25. The electrochemical cell of claim 24.

26. a semi-solid positive electrode comprising about 60% to about 80% by weight of an active material, about 1% to about 6% by weight of a conductive material, and about 20% to about 40% by weight of a non-aqueous liquid electrolyte, the semi-solid positive electrode having a thickness in the range of about 250 μm to about 2000 μm; a negative electrode comprising a high charge capacity material and having an overall capacity in the range of about 700 mAh / g to about 1200 mAh / g, the negative electrode having a thickness in the range of about 20% to about 25% of the thickness of the positive electrode; a separator disposed between the negative electrode and the semi-solid positive electrode; An electrochemical cell comprising:

27. The positive electrode has a thickness in the range of about 300 μm to about 600 μm.

27. The electrochemical cell of claim 26.

28. The negative electrode has a thickness in the range of about 60 μm to about 150 μm.

27. The electrochemical cell of claim 26.

29. the high capacity material comprises at least one material selected from tin, silicon, antimony, aluminum, and titanium oxide; 27. The electrochemical cell of claim 26.

Citation Information

Patent Citations

  • Thin lithium battery with slurry cathode

    JP2002540568A

  • Storage battery

    JP2010092636A

  • Asymmetric battery with semi-solid positive electrode and high energy density negative electrode

    JP2016511521A

  • Asymmetric battery having semi-solid cathode and high energy density anode

    JP2020115459A

  • Asymmetric battery with semi-solid cathode and high energy density anode

    JP2022118733A